Cottingam’s Conception of Descrates’s Trialism and Modern Discussions - Bodnarchuk, Lubov; Sen’, Anastasia (Sententiae, 2014)
The approaches of the main interpreters of Cartesianism as trialism (J. Cottingam, D. Hoffman, T. Schmaltz, etc.) and the critisism of their ideas made by supporters of dualistic interpretation of Cartesianism (M. Rozemond, etc.) are described in the article. Significant changes in the current interpretation of dualism caused by controversy with trialism are marked.